Healthcare workers’ perceptions of postoperative care and implementation challenges in conflict-affected northwest Syria: a mixed-methods analysis - Gilbert Burnham; Bara Zuhaili; Stefany M Lazieh; Maia C Tarnas; Kelli Wagner; Ismail Alkhatib; Camila Polinori; Measser Netfagi; Ahmad Ghandour; Sameeh Qaddour (BMJ Public Health)
Introduction Protracted violent conflict has severely reduced healthcare provision in northwest Syria (NWS), and this is especially concerning for postoperative care as conflict-related injuries have further compounded this strain. Without sufficient postoperative care, minor complications can evolve into life-threatening events. In this study, we aim to understand healthcare workers’ attitudes, practices and perceptions regarding postoperative care in NWS and identify key barriers to postoperative care.Methods Individuals with experience in health leadership positions in NWS were identified using purposive and snowball sampling and interviewed using a semistructured interview guide. Interview summaries were analysed using a standardised codebook to identify potential themes. In addition to these interviews, an online survey on hospital practices was sent to hospital administrators and non-governmental organisation leadership who disseminated the survey to all employees engaging in clinical work.Results Eighteen key informants were interviewed, and 466 survey responses from doctors (39%), nurses (37%), medical technicians (13%) and administrators (11%) were recorded. Through key informant interviews, we demonstrate several barriers to postoperative care, including health system fragmentation, limited healthcare workforce, insufficient resources due to conflict, disinterest, and lack of clinical documentation and discharge standards. Survey respondents reported poor patient compliance (66%), lack of routine follow-up visits (42%) and non-sterile operating room instruments (42%) as primary reasons for postoperative complications. Identified pathways to improve postoperative care included increased staffing and training, improved operating room sterilisation, and enhanced patient follow-up and discharge processes.Conclusion In conclusion, the health system in NWS is extremely overburdened from over a decade of violent conflict, increased demand for health services and insufficient resources. This has made implementing consistent and adequate postoperative care nearly impossible, contributing to unnecessary complications and mortality. Solutions to address postoperative complications in NWS must account for these complex realities and the broader context in which this system exists.